Behavior of drag anchor in clay with linearly increasing shear strength under unidirectional and combined loading. (February 2017) - Wu, Xiaoni; Chow, Yean Khow; Leung, Chun Fai
Highlights: A comprehensive study of drag anchor capacity factors in in homogeneous clay under unidirectional vertical, horizontal and rotational loading. The effects of soil non-homogeneity factor and anchor embedment depth ratio are investigated. The effects of soil overburden pressure ratio and the interface breakaway condition are investigated. The effect of soil non-homogeneity on the yield envelopes for deep and shallow anchor behavior is studied. The effect of both the rough and smooth interface conditions on the yield envelopes is studied. Abstract: Drag anchor is a widely used economical anchor option for offshore floating structures. The anchor behavior under unidirectional loading and combined loading is important for anchor selection. The anchor behavior under combined loading, characterized by the yield envelope, can also be used for the prediction of anchor installation, which is still an issue in anchor design. However, most existing studies on anchor capacity are for plate anchors which focused only on the anchor pullout capacity in soil with uniform shear strength. The behavior of drag anchor under unidirectional and combined loading in soil with linearly increasing shear strength profile is seldom investigated. The current 2D finite element studies investigate the anchor behavior for a horizontal anchor fluke in clay with linearly increasing shear strength under unidirectional vertical, horizontal and rotational loadings first. Then based on the results of anchor unidirectional loading behavior, the yield envelopes for anchor under combined loading for both shallow and deep embedded flukes are studied. The effect of anchor embedment depth, soil non- homogeneity, soil overburden pressure and the soil/anchor interface breakaway conditions are studied to provide insight for drag anchor design.